First Report of Didymella sinensis Causing Leaf Blight on Italian Ryegrass in China - Liu, Jiaqi; Long, Zhongfu; Xue, Longhai; Li, Chunjie (Plant disease, 2023)
Italian ryegrass ( Lam.) is a high-yield, high-quality forage grass and is cultivated widely in southern China. In April 2021, small black spots were observed on leaves of Italian ryegrass in the field of about 300 ha located in DuShan county, Guizhou province, China (25.62056°N, 107.53139°E). Approximately 1 to 3% of plants were affected. For isolation, eleven tissue pieces (about 0.5 × 1 cm) from four symptomatic leaves were surface-disinfested in 75% ethanol solution for 40s, rinsed thrice in sterilized distilled water and air dried; then these tissues were plated on potato dextrose agar (PDA), and incubated at 25°C for 4 days in the dark. Nine fungal isolates with similar colony characteristics were obtained, and three representative isolates (LMDS1, LMDS2 and LMDS3) were selected for further study. Colonies on PDA were 47 to 57 mm diam after 5 days, margin regular, dark gray in the center surrounded by white to gray, with floccose aerial mycelia on the upper side, and dark brown to black on the reverse side. There was no fungal sporulation when these isolates were incubated under continuous ultraviolet light on PDA, oatmeal agar (OA), malt extract agar (MEA) and potato carrot agar (PCA). ITS-rDNA, LSU-rDNA, and two other protein-coding genes ( and ) were amplified with primers described by Chen et al. (2017). Sequences were deposited in GenBank (ON692740 to ON692742 for ITS, ON692775 to ON692777 for LSU, ON704660 to ON704662 for , and ON704657 to ON704659 for ). BLAST analysis of all these four segments showed >99.7% identity with those sequences of ex-type isolate CGMCC 3.18348 of (Chen et al. 2017; Hou et al. 2020). Maximum likelihood (RAxML) phylogenetic tree based on the combined ITS, LSU, and alignments also showed these three isolates and the other two reported isolates formed a subclade with 100% bootstrap support. Referring to our previous method (Xue et al. 2020), five 8-week-old healthy plants of Italian ryegrass were spray-inoculated separately with a mycelial suspension of about 1.5 × 10 CFU/ml. In addition, five plants considered as non-inoculated controls were sprayed with sterilized distilled water. All plants were individually covered with transparent polyethylene bags for 5 days to maintain high relative humidity and placed in a greenhouse at 23 to 26°C. The small black spots similar to those observed on infected plants in the field developed on leaves fifteen days after inoculation. The symptoms consisted of brown to dark brown spots when leaves were severely infected; however, symptoms were not observed on non-inoculated plants (controls). Pathogenicity tests were carried out three times. The same fungus was re-isolated from the lesions, and confirmed by morphological characterization and molecular technique as described above, thus fulfilling Koch's postulates. To the best of our knowledge, this is the first report of causing leaf blight on Italian ryegrass in China. The accurate identification of this pathogen would be useful for the prevention and control of leaf spot on Italian ryegrass in the future.